Containment and denial: raising awareness of unconscious processes present when teachers are working with children and families where there is domestic abuse. Issue 4 (2nd October 2018) - Ellis, Gemma
ABSTRACT: This paper reports a small-scale, mixed methods research project exploring the perceptions and experiences of primary school teachers regarding domestic abuse. The paper focuses on the psychoanalytic concepts of containment and denial present in such situations. Questionnaire findings suggested that there was a significant difference between teachers who had attended relevant training and those who had not in their confidence levels in 1) responding to disclosures, and 2) recognising whether a child was exposed to domestic abuse ( n  = 165). Semi-structured interviews, analysed using thematic analysis, were carried out with experienced teachers ( n  = 8). Four overarching themes were identified: emotional factors of the teacher's role; working within the school system; the relationship with the child and family; and uncertainty about what teachers need to know. Findings are discussed in relation to the psychoanalytic concepts of containment and denial. Implications for practice, identifying the roles of unconscious processes and holistic containment, are discussed.